1991
DOI: 10.1093/infdis/163.2.233
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors in Male-Female Sexual Transmission of Human Immunodeficiency Virus Type 1

Abstract: In a study of human immunodeficiency virus type 1 (HIV-1)-uninfected African prostitutes, 83 (67%) of 124 seroconverted to HIV-1. Oral contraceptive use (odds ratio [OR], 3.1; 95% confidence interval [CI], 1.1-8.6; P less than .03), genital ulcers (mean annual episodes, 1.32 +/- 0.55 in seroconverting women vs. 0.48 +/- 0.21 in seronegative women; P less than .02) and Chlamydia trachomatis infections (OR, 3.6; CI, 1.3-11.0; P less than .02) were associated with increased risk of HIV-1 infection. Condom use red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
256
1
11

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(270 citation statements)
references
References 17 publications
2
256
1
11
Order By: Relevance
“…Chanchroid Chlamydia, Syphilis or Herpes virus infections) are aligned with increased HIV seroprevalence (UNAIDS, 1998, Hook et al, 1992Plummer et al, 1991) could be tight to abrasions at the site of entry in the vagina or anal canal. Heise et al (1991) however reported that HIV could directly infect the bowel mucosa and perhaps cervical epithelium without the need for ulcerations which gave clue to the relatively low risk of the mucosal lining of the foreskin, urethral canal and oral genital contact (through minimal) to be implicated (Winkelstein et al, 1987).…”
Section: Horizontal (Heterosexual) Transmissionmentioning
confidence: 99%
“…Chanchroid Chlamydia, Syphilis or Herpes virus infections) are aligned with increased HIV seroprevalence (UNAIDS, 1998, Hook et al, 1992Plummer et al, 1991) could be tight to abrasions at the site of entry in the vagina or anal canal. Heise et al (1991) however reported that HIV could directly infect the bowel mucosa and perhaps cervical epithelium without the need for ulcerations which gave clue to the relatively low risk of the mucosal lining of the foreskin, urethral canal and oral genital contact (through minimal) to be implicated (Winkelstein et al, 1987).…”
Section: Horizontal (Heterosexual) Transmissionmentioning
confidence: 99%
“…In Africa, the early identification and utilization of core groups of the population, particularly sex workers, to monitor the epidemic led to a consideration of popula-tion mixing patterns. [33][34][35][36] In efforts to more fully understand the dynamics underlying observed population mixing patterns, researchers have begun to focus on environmental factors, such as migratory labor practices, which facilitate transmission through the geographic diffusion and mixing of populations with varying HIV prevalences. [37][38][39][40][41] For example, investigators in Thailand found that 25% of truckers in their study had had sex with commercial sex workers, as well as with other female partners, such as their wives.…”
Section: Understanding Hiv Sexual Transmission In the Context Of Devementioning
confidence: 99%
“…Research conducted with core group populations has helped document the fact that STIs are potent biological cofactors in the sexual transmission of HIV. 34,36,43 However, HIV-preventive interventions targeted at STI control in generalized epidemics 34,44,45 have had dramatically different results, suggesting the need for further specification of the phase of the epidemic to improve understanding of transmission dynamics and the timing of specific interventions. 46 These data suggest that STI control may be only one component of multimethod and multilevel approaches to preventing HIV infection.…”
Section: Understanding Hiv Sexual Transmission In the Context Of Devementioning
confidence: 99%
“…There are indications that the risk of re-infection after antibiotic treatment of a previous infection is high -13-26% [4]. Moreover, Ct enhances transmission of the human immunodeficiency virus (HIV) and may serve as a cofactor in human papilloma virus (HPV) infection [5,6]. This means that the control of Ct STIs may be possible only through the development of a safe and efficient vaccine.…”
Section: Introductionmentioning
confidence: 99%